Implementasi Asesmen dan Tindak Lanjut Dalam Pembelajaran Tahfiz di SDN 21 Kota Pariaman - Mutiara Heidi fernanda; Khadijah; Remiswal (Jurnal Ilmu Pendidikan, 2026)
Tahfiz Al-Qur'an learning at the elementary school level faces major challenges related to limited teacher-student ratios and the diversity of students' initial abilities. This study aims to deeply explore the implementation of assessment and follow-up strategies in tahfiz learning at Sekolah Dasar Negeri (SDN) 21 Pariaman City. Utilizing a qualitative approach with a descriptive case study design, data were collected through in-depth interviews with a single tahfiz teacher. The results indicate that despite limited time and teacher ratios, learning is implemented effectively by integrating sama'i, talaqqi, tikrar, and tasmi' methods combined with the utilization of Smart TV as an interactive medium. Assessments are conducted periodically, covering fluency (hifzhon), tajwid accuracy, and articulation eloquence (fashohah). Follow-up strategies for students who do not achieve mastery are implemented through a persuasive-humanistic approach, offering flexible extended timeframes to complete targets gradually and establishing active collaboration with parents for muraja'ah at home. The novelty of this research lies in the assessment synchronization model based on students' field abilities combined with interactive technology to overcome teacher limitations. This study concludes that an approach prioritizing children's psychological comfort over curriculum targets successfully maintains the quality standards of Juz 30 memorization while sustaining students' learning motivation. This model can serve as a tactical reference for other elementary education institutions facing similar constraints.